2020
DOI: 10.1021/acsomega.9b03479
|View full text |Cite
|
Sign up to set email alerts
|

Privileged Scaffold Chalcone: Synthesis, Characterization and Its Mechanistic Interaction Studies with BSA Employing Spectroscopic and Chemoinformatics Approaches

Abstract: Chalcone, a privileged structure, is considered as an effective template in the field of medicinal chemistry for potent drug discovery. In the present study, a privileged template chalcone was designed, synthesized, and characterized by various spectroscopic techniques (NMR, high-resolution mass spectrometry, Fourier transform infrared (FT-IR) spectroscopy, UV spectroscopy, and single-crystal X-ray diffraction). The mechanism of binding of chalcone with bovine serum albumin (BSA) was determined by multispectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 81 publications
0
30
0
Order By: Relevance
“…These results are in line with another data 43 , 47 and our previously published studies 48 . Moreover, in silico and in vitro studies validated the moderate binding of chalcone with BSA 49 , 50 . Molecular docking and molecular dynamic simulation studies suggested the stabile binding of chalcone with the BSA microenvironment 49 .…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…These results are in line with another data 43 , 47 and our previously published studies 48 . Moreover, in silico and in vitro studies validated the moderate binding of chalcone with BSA 49 , 50 . Molecular docking and molecular dynamic simulation studies suggested the stabile binding of chalcone with the BSA microenvironment 49 .…”
Section: Resultsmentioning
confidence: 75%
“…Moreover, in silico and in vitro studies validated the moderate binding of chalcone with BSA 49 , 50 . Molecular docking and molecular dynamic simulation studies suggested the stabile binding of chalcone with the BSA microenvironment 49 . Major structural differences between the compounds used in our study are related to the ring C which correlates with binding to HSA.…”
Section: Resultsmentioning
confidence: 75%
“…Besides, it is a popular approach to substitute HSA with BSA to represent the serum albumins in protein ligand interaction studies. [ 35 ] We investigated the biophysical interactions of the chosen compound 4g with BSA through steady‐state absorption spectra. The absorption spectra of BSA show characteristic bands, at around 280 nm.…”
Section: Resultsmentioning
confidence: 99%
“…[ 61,62 ] The UV–vis absorption of R‐CDs and R‐CDs‐Cu 2+ (40 μM) system in Figure 5 (a) did not coincide, indicating that the mechanism of Cu 2+ quenching R‐CDs was the static quenching mechanism or the combination mechanism of static and dynamic quenching. [ 63 ] In addition, the dynamic quenching mechanism, the static quenching mechanism and the combination mechanism of static and dynamic quenching can be distinguished by measuring the fluorescence lifetime of the fluorescent probe before and after quenching. If the fluorescence lifetimes before and after quenching are the same, the quenching mechanism is static quenching mechanism, if the fluorescence lifetimes before and after quenching are different, the quenching mechanism is the dynamic quenching mechanism or the combination of static and dynamic quenching.…”
Section: Resultsmentioning
confidence: 99%